Perioperative exercise training in elderly subjects - Jack, S.; West, M.; Grocott, M.P.W. (Best practice & research. Clinical anaesthesiology, 2011)
The association between physical fitness and outcome following major surgery is well described – less fit patients having a higher incidence of perioperative morbidity and mortality. This has led to the idea of physical training (exercise training) as a perioperative intervention with the aim of improving postoperative outcome. Studies have started to explore both preoperative training (prehabilitation) and postoperative training (rehabilitation). We have reviewed the current literature regarding the use of prehabilitation and rehabilitation in relation to major surgery in elderly patients. We have focussed particularly on randomised controlled trials, systematic reviews and meta-analyses. There is currently a paucity of high-quality clinical trials in this area, and the evidence base in elderly patients is particularly limited. The review indicated that prehabilitation can improve objectively measured fitness in the short time available prior to major surgery. Furthermore, for several general surgical procedures, prehabilitation using inspiratory muscle training may reduce the risk of some specific complications (e.g., pulmonary complications and predominately atelectasis), but it is unclear whether this translates into an improvement in overall surgical outcome. There is clear evidence that rehabilitation is of benefit to patients following cancer diagnoses, in terms of physical activity, fatigue and health-related quality of life. However, it is uncertain whether this improved physical function translates into increased survival and delayed disease recurrence. Prehabilitation using continuous or interval training has been shown to improve fitness but the impact on surgical outcomes remains ill defined. Taken together, these findings are encouraging and support the notion that pre- and postoperative exercise training may be of benefit to patients. There is an urgent need for adequately powered randomised control studies addressing appropriate clinical outcomes in this field.